2005
DOI: 10.1055/s-2005-865649
|View full text |Cite
|
Sign up to set email alerts
|

Stress Fractures in the Juvenile Skeletal System

Abstract: Stress fractures affecting the juvenile skeletal system are rare and are described as having a good prognosis. Precisely because these fractures are so rare, studies allowing clear and generally applicable conclusions are lacking. The object of the present study was a systematic analysis of patients with stress fractures in an immature skeletal system, with special reference to the frequently difficult and delayed diagnosis and to the forms of therapy considered appropriate. Twenty-five patients with a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 20 publications
1
24
0
2
Order By: Relevance
“…The observations of other authors are similar: in the material presented by Papadimitriou, this time was 25 days on average [6]. From among 27 patients with stress fractures presented in the study published by Niemeyer, in 13 persons the diagnosis was established within 2 weeks, while this period was over 2 weeks in the remaining group of patients [14].…”
Section: Wnio Skisupporting
confidence: 66%
See 1 more Smart Citation
“…The observations of other authors are similar: in the material presented by Papadimitriou, this time was 25 days on average [6]. From among 27 patients with stress fractures presented in the study published by Niemeyer, in 13 persons the diagnosis was established within 2 weeks, while this period was over 2 weeks in the remaining group of patients [14].…”
Section: Wnio Skisupporting
confidence: 66%
“…In ni au to rzy ma j膮 po dob ne ob ser wa cje: w ma te ria le Pa pa di mi triou by 艂o to 艣red -nio 25 dni [6]. Spo 艣r贸d 27 cho rych ze z艂a ma nia mi zm臋 cze nio wy mi przed sta wio ny mi w pra cy Nie mey era roz po zna nie u 13 z nich po sta wio no przed up艂y wem 2 ty go dni, za艣 u po zo sta 艂ych po wy 偶ej 2 ty go dni [14].…”
Section: Discussionunclassified
“…Thus, damage due to repeated loading is of considerable interest for biological tissues as cracking is observed for loads far below the static strength. Cyclic failures of bones due to the accumulation of fatigue damage are clinically known as overuse injuries or stress fractures which are observed in athletes (Snyder et al, 2006;Niemeyer et al, 2006) and military recruits (Sormaala et al, 2006) and are also associated with age related fragility fractures (Burr et al, 1997). Cyclic loading induced damage accumulation is also reported to weaken vertebrae (Burr et al, 1997) and is often associated with loosening of implants (Bauer and Schils, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…In another Japanese study 29 of stress fractures in 208 athletes under the age of 20 years, the researchers found that the peak age of occurrence was 16 years, the most frequent site was the tibial shaft, and basketball was the sport most commonly associated with stress fractures. A 2006 retrospective study 47 of stress fractures among 25 juveniles demonstrated that the age of onset was 12.9 6 4.3 years (range, 3-17 years) and the tibia was most often affected (48%, n 5 13), followed by the metatarsals (18.5%, n 5 5). Using data from the High School Report Injuries Online (RIO) injury surveillance system, Fernandez et al 48 reported that 4350 athletic injuries occurred among athletes participating in 9 high school sports during 1 academic year.…”
Section: Injury Surveillancementioning
confidence: 99%